Simulation of Runoff in Air Putih, Terengganu Based on Hydrologic Modelling System (HEC-HMS) - Mohd Yasin, Ikmal Hisyam; Hamidon, Nuramidah; Maizzaty Abdullah (Progress in Engineering Application and Technology, 2025)
Flooding is a serious global risk that is becoming more common in Malaysia. It has resulted in property destruction and fatalities. It is one of the tragedies of nature that hinders the development of Air Putih, Terengganu. Hence, the aims of this investigation were to develop the hydrologic model for Kemaman River Sub—basin and evaluate the runoff with make the calibration, validation and simulation by using Hydrologic Engineering Centre – Hydrologic Modelling System (HEC-HMS). Following the development of the hydrologic model for Air Putih, the model was calibrated and validated using the coefficient of determination, R2, which yielded values of 0.84 and 0.72 respectively, the R2 value is close to 1, therefore it is proved that the data is trustable. Subsequently, the model was employed to simulate the runoff by using HEC-HMS. By using the rainfall and discharge data from SPRHiN, the results of run-off simulation process, it showed that the process is verified and reliable because the simulated flow in HEC-HMS is closely fit to the observed flow, which the R2 is 0.81. Based on the results, it is evident that Air Putih is a high-risk flood zone that is susceptible to flooding in the event of excessive rainfall in the area. Therefore, the implementation of HEC-HMS is effectively simulates the overall runoff pattern and provides a framework for understanding hydrological responses in Air Putih, Terengganu and the R² value demonstrates that the model aligns well with observed flow trends, indicating its utility for initial assessments.